Genetic Environment of blaTEM-1, blaCTX-M-15, blaCMY-42 and Characterization of Integrons of Escherichia coli Isolated From an Indian Urban Aquatic Environment - Singh, Nambram S.; Singhal, Neelja; Virdi, Jugsharan S. (Frontiers in Microbiology, 2018)
Presence of antibiotic resistance genes including those expressing ESBLs and AmpC-β-lactamases in Escherichia coli inhabiting the aquatic environments is a serious health problem. The situation is further complicated by the fact that antibiotic resistance genes can be easily transferred among bacterial species with the help of mobile genetic elements - plasmids, integrons, insertion sequences (IS) and transposons. Therefore, the analysis of genetic environment and mobile genetic elements associated with antibiotic resistance genes is important as these provide useful information about the epidemiology of these genes. In our previous study, we had reported presence of various β-lactam resistance genes present in E. coli strains inhabiting the river Yamuna traversing the National Capital Territory of Delhi (India). In the present study, we have analyzed the genetic environment of three antibiotic resistance genes blaTEM-1, blaCTX-M-15, and blaCMY-42 of those E. coli strains. The structure of class 1 integrons and their gene cassettes was also analysed. Insertion sequence IS26 was present upstream of blaTEM-1, ISEcp1 was present upstream of blaCTXM-15 gene and orf477 was present downstream of blaCTXM-15. ISEcp1 was also present upstream of blaCMY-42 and, blc and sugE genes were present in the downstream region of this gene. Thus, the overall genetic environment surrounding these genes was similar to that reported from E. coli strains isolated globally. Conjugation assays, isolation and analysis of plasmid DNA of the transconjugants indicated that blaTEM-1, blaCTX-M-15, blaCMY-42 and class 1 integron were plasmid-mediated and possibly transmit between genera through horizontal gene transfer (HGT). This might lead to dissemination of antimicrobial resistance genes in aquatic environment. The work embodied in this paper is the first describing the genetic environment of bla and integrons in aquatic E. coli isolated from India.